2016
DOI: 10.3892/ol.2016.4602
|View full text |Cite
|
Sign up to set email alerts
|

miR-199a-5p induces cell invasion by suppressing E-cadherin expression in cutaneous squamous cell carcinoma

Abstract: A growing quantity of evidence exists to suggest that microRNAs are significant regulators of multiple cellular processes. When expressed aberrantly in different types of cancer, including cutaneous squamous cell carcinoma (cSCC), they play key roles in tumorigenesis and progression. The aberrant expression of miR-199a-5p has been observed to contribute to carcinogenesis in various types of cancer. However, the role of miR-199a-5p in the progression of cSCC metastasis remains largely unknown. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Furthermore, the expression of RETREG1 was negatively regulated by miR-186 in CSCC cells, and restoration of RETREG1 attenuated the effects of miR-186 on CSCC cells. In recent decades, a large number of miRs, including, miR-125b (11), miR-365 (20), miR-205 (21), miR-199a-5p (22), and miR-203 (23) have been identified as key regulators of the development and progression of CSCC and numerous other types of human cancer. For instance, miR-199a-5p induces CSCC cell invasion by suppressing E-cadherin expression (22).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of RETREG1 was negatively regulated by miR-186 in CSCC cells, and restoration of RETREG1 attenuated the effects of miR-186 on CSCC cells. In recent decades, a large number of miRs, including, miR-125b (11), miR-365 (20), miR-205 (21), miR-199a-5p (22), and miR-203 (23) have been identified as key regulators of the development and progression of CSCC and numerous other types of human cancer. For instance, miR-199a-5p induces CSCC cell invasion by suppressing E-cadherin expression (22).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs, another type of non-coding small RNA that are 22-25 nucleotides in length, regulate the expression of their target genes through directly binding to the complementary sites in the 3'-UTR region of target mRNAs (25)(26)(27). Similar to lncRNAs, miRs are also associated with various cancers (28)(29)(30)(31)(32). For instance, a previous study demonstrated that miR-33a-5p increased the radiosensitivity of melanoma cells by inhibition of glycolysis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Given that miRs function through regulating the expression of their target genes (28,29), bioinformatics analysis was conducted to predict the potential target gene of miR-28-5p. We selected HOXB3 for the following studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that miRNAs function via regulating their target protein by binding to the 3’ untranslated regions (UTRs) of target messenger RNAs (mRNAs), resulting in mRNA degradation or the blockade of mRNA translation . Previously, miR‐199a‐5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia‐inducible factor 1 alpha (HIF‐1α), E‐cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin‐dependent kinase inhibitor 1C (P57, CDKN1C) …”
Section: Discussionmentioning
confidence: 99%
“…In present study, we showed that miR-199a-5p, frequently down- 19,20 Previously, miR-199a-5p was reported to functions as a tumor suppressor by targeting connective tissue growth factor (CTGF), integrin β1, hypoxia-inducible factor 1 alpha (HIF-1α), E-cadherin, hexokinase 2, frizzled class receptor 6 (FZD6), E2F transcription factor 3 (E2F3), Wnt family member 2 (WNT2) and cyclin-dependent kinase inhibitor 1C (P57, CDKN1C). [21][22][23][24][25][26][27][28][29] Clathrin is considered the prototype vesicle coat protein whose self-assembly mediates sorting of membrane cargo and recruitment of lipid modifiers. 30 In the past decades, most of studies were focused on clathrin mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%